2012
DOI: 10.1088/0963-0252/21/2/024007
|View full text |Cite
|
Sign up to set email alerts
|

Influence of target surfaces on the atomic oxygen distribution in the effluent of a micro-scaled atmospheric pressure plasma jet

Abstract: Micro-scaled plasma jets with reactive process gases, e.g. oxygen, are applied for localized surface treatment. Here, investigations of the development and the spatial distribution of atomic oxygen are reported in the post-discharge effluent of a micro-scaled atmospheric pressure plasma jet. These measurements are supplemented by installation of planar targets of various materials in the effluent. The reactive species are detected by means of two-photon laser-induced fluorescence spectroscopy from the discharg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 32 publications
3
16
0
Order By: Relevance
“…Now not only the ozone but also some short-living active species, such as, atomic oxygen and OH radical may interact with the central part of the substrate leading to an enhanced hydrophilicity. As shown in [14,36] the atomic oxygen can actually spread up to 2.0-2.5 mm way from the plasma column. The computer modeling of active species generated by Ar plasma jet in [31] predicted that along the gas flow oxygen atoms could cover even larger distances (∼ cm).…”
Section: Polymer Wettabilitymentioning
confidence: 93%
See 2 more Smart Citations
“…Now not only the ozone but also some short-living active species, such as, atomic oxygen and OH radical may interact with the central part of the substrate leading to an enhanced hydrophilicity. As shown in [14,36] the atomic oxygen can actually spread up to 2.0-2.5 mm way from the plasma column. The computer modeling of active species generated by Ar plasma jet in [31] predicted that along the gas flow oxygen atoms could cover even larger distances (∼ cm).…”
Section: Polymer Wettabilitymentioning
confidence: 93%
“…Since the UV photons propagate preferentially along the plasma column they would rather interact only with the target surface that is located just under the plasma jet [33]. As shown in [36] besides the VUV/UV radiation the long-lived active species, like O 3 can also reach the surface and spread radially over a large area of the sample. As can be noted in Fig.…”
Section: Polymer Wettabilitymentioning
confidence: 98%
See 1 more Smart Citation
“…It has been shown that this microplasma jet, under selected conditions, is operated in a homogeneous α-mode glow [17] with typical plasma densities around − 10 cm 11 3 [2,18,19]. This jet has already been used with He/O 2 and He/N 2 gas mixtures, where production of O, N, or O 3 has already been investigated by TALIF and MBMS [20][21][22][23]. The coordinate system used in this work has its origin (0,0,0) at the exit of the jet.…”
Section: μ-Appj With Bubbler Systemmentioning
confidence: 99%
“…Thus, measurements in direct vicinity to the surface are essential. Comparable measurements of the atomic-oxygen density in front of a target surface, in the effluent of the helium-driven μ-APPJ, offer a clue to this problem [42]. Here, dependent on the target material, a broadening of the radial oxygen distribution close to the surface was measured.…”
Section: Plasma Diagnosticmentioning
confidence: 99%